Terrorism and political violence : a sourcebook - Sondhi, M. L.; Indian Council of Social Science Research (New Delhi : Har-Anand Publications, 2000)
Papers presented at a national forum on 2-3 Mar. 2000 in New Delhi.
"Indian Council of Social Science Research."
Keywords: Terrorism -- India; Violence -- India; India -- Politics and government -- 1977-